2016
DOI: 10.4172/2324-8661.1000161
|View full text |Cite
|
Sign up to set email alerts
|

Omura's whale Balaenoptera omurai stranding on Qeshm Island, Iran, Persian Gulf:Further Evidence for a Wide (Sub) Tropical Distribution

Abstract: A small, juvenile rorqual live-stranded on Qeshm Island, Iran, in the northern Strait of Hormuz (Persian Gulf) in September 2007. Cause of stranding remains unknown but the whale (QE22.09.2007) showed no severe traumatic injuries nor was emaciated. Based on at least seven morphological features, considered diagnostic in combination, allowed a positive identification as Omura's whale Balaenoptera omurai. Features included diminutive body size (397 cm), a large number of ventral grooves (n=82) extending caudad o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Western North Indian Ocean (see Figure 5 for Detail) Iran Based on direct external examination and photographs of a stranded specimen from Qeshm Island, Strait of Hormuz, Iran, Ranjbar et al (2016) identified a 3.97 m calf rorqual as an Omura's whale, however, no specimens were preserved from this whale. Omura's whales may not be common in this region as none were found nearby among 18 specimens from Oman that were genetically identified as either B. edeni edeni or B. edeni brydei (Kershaw et al, 2013).…”
Section: France/new Caledoniamentioning
confidence: 99%
“…Western North Indian Ocean (see Figure 5 for Detail) Iran Based on direct external examination and photographs of a stranded specimen from Qeshm Island, Strait of Hormuz, Iran, Ranjbar et al (2016) identified a 3.97 m calf rorqual as an Omura's whale, however, no specimens were preserved from this whale. Omura's whales may not be common in this region as none were found nearby among 18 specimens from Oman that were genetically identified as either B. edeni edeni or B. edeni brydei (Kershaw et al, 2013).…”
Section: France/new Caledoniamentioning
confidence: 99%
“…This in turn may explain similarities in pigmentation patterns such as those we observed and which at first sight appeared to differ from those of a few individuals from other areas where pigmentation patterns were partly visible (Western Australia, Persian Gulf) 10,11 . However, the skin of the Western Australian specimen had likely undergone post-mortem darkening 10 and the skin of the Persian Gulf specimen presented cuts, scratches and abrasions on part of its surface (we ascribe these injuries to a collision with a ship), erasing part of the pigmentation 11 . The fact that a similar three-dark chevrons pattern also characterized an individual documented from off Komodo island 1 and another one from off southern Sri Lanka 5 suggests that it is, at least, a pattern frequently encountered in Omura's whales from the Indian-Ocean.…”
Section: Resultsmentioning
confidence: 99%
“…Sightings of Omura's whale B. omurai have not yet been reported in the Arabian Sea and appear not to be among sightings of balaenopterids off Oman (Minton et al 2010), although a stranding has been reported off Iran (Ranjbar et al 2016). Omura's whale song has now been described for several locations from the mid-equatorial Atlantic to the Western Indian Ocean to the northwest coast of Australia, with consistent features across this range that are stereotyped and distinctly different from the novel songtype we describe here (Cerchio et al 2015, 2019.…”
Section: Species Attributionmentioning
confidence: 99%